Trends in surgical aortic valve replacement in pre- and post-transcatheter aortic valve replacement eras at a structural heart center - Norton, Elizabeth L.; Ward, Alison F.; Tully, Andy; Leshnower, Bradley G.; Guyton, Robert A.; Paone, Gaetano; Keeling, William B.; Miller, Jeffrey S.; Halkos, Michael E.; Grubb, Kendra J. (Frontiers in Cardiovascular Medicine, 2023)
Background The advent of transcatheter aortic valve replacement (TAVR) has directly impacted the lifelong management of patients with aortic valve disease. The U.S. Food and Drug Administration has approved TAVR for all surgical risk: prohibitive (2011), high (2012), intermediate (2016), and low (2019). Since then, TAVR volumes are increasing and surgical aortic valve replacements (SAVR) are decreasing. This study sought to evaluate trends in isolated SAVR in the pre- and post-TAVR eras. Methods From January 2000 to June 2020, 3,861 isolated SAVRs were performed at a single academic quaternary care institution which participated in the early trials of TAVR beginning in 2007. A formal structural heart center was established in 2012 when TAVR became commercially available. Patients were divided into the pre-TAVR era (2000–2011, n = 2,426) and post-TAVR era (2012–2020, n = 1,435). Data from the institutional Society of Thoracic Surgeons National Database was analyzed. Results The median age was 66 years, similar between groups. The post-TAVR group had a statistically higher rate of diabetes, hypertension, dyslipidemia, heart failure, more reoperative SAVR, and lower STS Predicted Risk of Mortality (PROM) (2.0% vs. 2.5%, p < 0.0001). There were more urgent/emergent/salvage SAVRs (38% vs. 24%) and fewer elective SAVRs (63% vs. 76%), (p < 0.0001) in the post-TAVR group. More bioprosthetic valves were implanted in the post-TAVR group (85% vs. 74%, p < 0.0001). Larger aortic valves were implanted (25 vs. 23 mm, p < 0.0001) and more annular enlargements were performed (5.9% vs. 1.6%, p < 0.0001) in the post-TAVR era. Postoperatively, the post-TAVR group had less blood product transfusion (49% vs. 58%, p < 0.0001), renal failure (1.4% vs. 4.3%, p < 0.0001), pneumonia (2.3% vs. 3.8%, p = 0.01), shorter lengths of stay, and lower in-hospital mortality (1.5% vs. 3.3%, p = 0.0007). Conclusion The approval of TAVR changed the landscape of aortic valve disease management. At a quaternary academic cardiac surgery center with a well-established structural heart program, patients undergoing isolated SAVR in the post-TAVR era had lower STS PROM, more implantation of bioprosthetic valves, utilization of larger valves, annular enlargement, and lower in-hospital mortality. Isolated SAVR continues to be performed in the TAVR era with excellent outcomes. SAVR remains an essential tool in the lifetime management of aortic valve disease.